The Moore thesis: what's left after 1989?. Issue 1 (2nd January 2016) - Bernhard, Michael
Abstract : This article reconsiders the work of Barrington Moore and his critics on the historical emergence of democracy in the light of post-communist democratization. What are we to make of a region which violates Moore's dictum – "No bourgeoisie, no democracy"? Using the tools of comparative historical analysis, it makes sense of how democracy emerged in the region by developing a theory which both explains why this was possible and what social actors were essential to this outcome. With attention to patterns of social development in the region, the politics of elite alliance in the final phase of communism, the strength of civil society at extrication, and the role of the international system, it explains differences in regime outcomes across the region.